Seeking a reflexive space for teaching to and about diversity: emergent properties of enablement and constraint for teacher educators. Issue 2 (17th February 2019) - Ryan, Mary; Bourke, Terri; Lunn Brownlee, Jo; Rowan, Leonie; Walker, Sue; Churchward, Peter
ABSTRACT: The recasting of teaching as a technical enterprise rather than as a space for intelligent problem-solving means that governments around the world will continue to pursue agendas to regulate and prescribe teacher education. Teacher education reform has been attempted for over 30 years in many countries around the world, yet the crucial priority of preparing teachers for increasingly diverse classrooms has not been addressed. We used reflexivity theory and an innovative social lab methodology to investigate the conditions of teacher education experienced by 12 teacher educators at a metropolitan university in Australia. Personal, structural and cultural emergent properties were evident and were experienced variously as both enablements and constraints. Our findings show that these teacher educators were more constrained than enabled in their reflexivity for teaching to and about diversity. We argue that teacher educators need to form deep and enduring inquiry relationships with schools and communities in order to develop context-specific solutions to address the complexities of teaching to diversity.